The Proximate and Ultimate Composition of Pulverised Coconut Shell - Mat Isa, Norasikin; Nasir, Nurul Fitriah; Hazman, Nurhazwani (International Journal of Integrated Engineering, 2024)
Biomass is gaining traction as a renewable energy source as they play a major role in global green transition. Authors believe that coconut shell has a huge potential comparable to wood and sawdust in burning appliances. However, the use of coconut shell in combustion industry still limited and unconventional due to limited of studied and uncommonly practiced. Hence, the analysis of coconut shell on its properties is a must as well as to highlight the good side of coconut shell as a fuel. The coconut shell residues were collected, dried, purified, crushed and grinded to obtain in pulverised form. Then, the sample of pulverised coconut shell was undergo the proximate and ultimate analysis based on standard needs (ASTM E871, E872 and D1102). The results obtained were compared to other types of fuel. From the comparison findings, coconut shell has a huge potential to be utilize as fuel due to its low moisture content, low ash content, higher heating value and has sustainably sourced in Malaysia.